Radio-sulphur (35S) detection by LSC: how to deal with interfering natural radionuclides - Schubert, Michael; Kopitz, Jürgen (Journal of environmental radioactivity, 2025)
Naturally occurring radio-sulphur (35S) is suitable as an aqueous environmental tracer for the dating of groundwater and surface waters with residence times of less than one year. As a β-decaying radionuclide, 35S is detected using liquid scintillation counting (LSC). When extracting 35S as sulphate from large-volume water samples, there is the possibility of unintentional co-extraction of other naturally occurring radionuclides, which interfere with the measurement of 35S by LSC. The most important of these radionuclides are (i) 226Ra, (ii) the short-lived progeny of 222Rn, (iii) 210Pb and its progeny and (iv) 3H. In addition, 14C, which might be present in scintillation cocktails or LSC plastic vials, and 40K, which is likely to be present in LSC glass vials, can have a significant impact on the LSC detection result. There are a few publications that address sample preparation for 35S detection with LSC. However, the published datasets do not contain sufficiently detailed information to pursue the issue of potential interferences of the said naturally occurring radionuclides with the 35S signal. In our study, we measured standardized samples containing the said radionuclides by LSC, evaluated location, shape and overlap of the associated energy peaks, and assessed the possible influences of the individual nuclides on the 35S detection results. The findings of our study show that when measuring 35S obtained from a natural water sample, counts detected in the 35S energy window cannot be unconditionally interpreted as actual 35S counts. Interfering nuclides (especially 3H, 14C, 40K, and 210Pb) can lead to counts in the 35S energy window and thus to an overestimation of the 35S activity concentration of the water sample (and consequently to an underestimation of the water age). We therefore recommend generally a complete evaluation of the LSC spectrum in order (i) to be able to infer the potential presence of other radionuclides in the measured sample, and (ii) to evaluate the DPM counted in the 35S energy window accordingly, as these may contain counts of the aforementioned interfering radionuclides.